Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 164 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Calomyscus Thomas, 1905", "Country is Iran (Islamic Republic of)", "HasCoordinate is true" ] } The dataset includes 164 records from 5 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0022831-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences